Use of symptom screening and sputum microscopy testing for active tuberculosis case detection among HIV-infected patients in real-world clinical practice in Uganda - Roy, Monika; Muyindike, Winnie; Vijayan, Tara; Kanyesigye, Michael; Bwana, Mwebesa; Wenger, Megan; Martin, Jeffrey; Geng, Elvin (Journal of acquired immune deficiency syndromes, 2016)
Background: The uptake of intensified active TB case finding among HIV-infected patients using symptom screening is not well understood. We evaluated the rate and completeness of each interim step in the TB “diagnostic cascade” to understand real-world barriers to active TB case detection. Methods: We conducted a cohort analysis of new, ART-naïve, HIV-infected patients who attended a large HIV clinic in Mbarara, Uganda (March 1, 2012 – September 30, 2013). We used medical records to extract the date of completion of each step in the diagnostic cascade: symptom screen, order, collection, processing, and result. Factors associated with lack of sputum order were evaluated using multivariate Poisson regression and a chart review of 50 screen positive patients. Results: Of 2613 patients, 2439 (93%) were screened for TB and 682(28%) screened positive. Only 90(13.2%) had a sputum order. Of this group, 83% completed the diagnostic cascade, 13% were diagnosed with TB, and 50% had a sputum result within 1 day of their visit. Sputum ordering was associated with WHO Stage 3 or 4 HIV disease and greater number of symptoms. The main identifiable reasons for lack of sputum order in chart review were treatment for presumed malaria (51%) or bacterial infection (43%). Conclusions: The majority of newly enrolled HIV-infected patients who screened positive for suspected TB did not have a sputum order, and those who did were more likely to have more advanced HIV disease and symptoms. Further evaluation of provider behavior in the management of screen positive patients could improve active TB case detection rates.
Keywords: Symptom screening; HIV-infected patients; Uganda; Active TB